Present of Causal Model of Effective Cognitive Factors on Academic Dishonesty with Emphasize on Self-Efficiency Mediating Role and Metacognitive of First Secondary School Students in Shira - Talebi, Saeed (International Journal of Psychosocial Rehabilitation, 2020)
The aim of current research was presenting causal model of effective psychology factors on academic dishonesty with emphasize on self-efficacy and metacognitive of Shiraz first secondary school students. According to, chose 360 of Shiraz first secondary school students by random-stratified sampling method and answered to academic dishonesty questionnaires as Mc Cabe & Trenive (2000), academic self-efficacy beliefs (ASEBQ) by Zajacova et al. (2005), Ryan & Frederick vitality (1997) and Baer et al. mindfulness (2006). Data analysis was performed by path analytical method and AMOS software. Data analysis results showed mindfulness direct effect on metacognitive is 0/29. Addition to, direct effect of emotional intelligence (0/19) on academic selfefficacy (0/21) is significant. While direct effect of mental vitality on metacognitive is 0/24 and direct effect of metacognitive on academic dishonesty is -0/34. So, current research results show suitable fit of causal model of effective cognitive psychology factors on academic dishonesty of Shiraz first secondary school students.